Substitusi Parsial dan Full Semen Konvensional pada Campuran Beton Geopolimer Berbahan Baku Arang Cangkang Kelapa Sawit - Aprilia, Rina; Liliana, Liliana; Frieda, Frieda (Jurnal Talenta Sipil, 2025)
CKS charcoal is waste from burning CKS as operational fuel for Asphalt Mixing Plant (AMP). Hampangen clay and CKS charcoal are usually used as raw materials for non-conventional cement mixed with fine aggregate and coarse aggregate which are usually used in the Palangka Raya City environment. Several studies have been conducted by utilizing industrial by-products as non-conventional cement and made as a geopolymer concrete mixture. The geopolymer concrete mixture uses aggregates that are usually used in Palangka Raya City.This study aims to determine whether by adding conventional cement partially and fully to a mixture of non-conventional cement made from Hampangen clay and CKS charcoal can produce a geopolymer concrete mixture that is maximum in terms of the compressive strength of the concrete produced. The method used is the calculation of the mix design calculated using the ACI method (meaning in conditions of adding conventional cement fully - 100%). Based on the results of the study, it is known that the addition of PCC cement, the Gresik brand, in a mixture of geopolymer concrete made from CKS charcoal and Hampangen clay on the compressive strength of concrete is categorized as very strong.